Rancang Bangun Aplikasi Penentuan Harga Jual Berdasarkan Metode Full Costing Pada UD. Surya Mandiri Nusantara - Wardana, Dwi Kusuma; Widodo, Arifin Puji; Sukmaaji, Anjik (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
UD. Surya Mandiri Nusantara is currently producing and selling non cholesterol duck. In the process of production and sales is no process of determining the cost of production and selling price determination, but have difficulty in determining the selling price because there is no knowing whether the calculations for this with his own method right. Based on the above problems, the proposed Design Build Applications Selling Price Method Based Full Costing At UD. Surya Mandiri Nusantara which can process data production and sales as appropriate. Applications built to display reports the cost of production, calculation of ROI (return of investment as), the expected profit, sales price calculation appropriately using the full costing method.Â